2022
DOI: 10.1111/ajt.16822
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and long-term outcomes of cytomegalovirus DNAemia and disease in pediatric solid organ transplant recipients

Abstract: Despite prevention strategies, cytomegalovirus (CMV) remains a common infection in pediatric solid organ transplant recipients (SOTR). We sought to determine the frequency, associations with, and long‐term outcomes of CMV DNAemia in pediatric SOTR. We performed a single‐center retrospective cohort study, including 687 first time SOTR ≤21 years receiving universal prophylaxis from 2011 to 2018. Overall, 159 (23%) developed CMV DNAemia, the majority occurring after completing primary prophylaxis. CMV disease occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…This was the case for analyses involving all patients, as well as the subset of only at‐risk SOT recipients. This finding is consistent with a recent study by Valencia Deray and colleagues, who found that DNAemia was not associated with graft failure, all‐cause mortality, or other organ‐specific poor outcomes among 687 pediatric SOT recipients 9 . Although these authors found that rejection was more common among pediatric liver transplant recipients who experienced DNAemia, this association was not evaluated using multivariable analyses.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This was the case for analyses involving all patients, as well as the subset of only at‐risk SOT recipients. This finding is consistent with a recent study by Valencia Deray and colleagues, who found that DNAemia was not associated with graft failure, all‐cause mortality, or other organ‐specific poor outcomes among 687 pediatric SOT recipients 9 . Although these authors found that rejection was more common among pediatric liver transplant recipients who experienced DNAemia, this association was not evaluated using multivariable analyses.…”
Section: Discussionsupporting
confidence: 88%
“…Valencia Deray and colleagues, who found that DNAemia was not associated with graft failure, all-cause mortality, or other organ-specific poor outcomes among 687 pediatric SOT recipients. 9 Although these authors found that rejection was more common among pediatric liver transplant recipients who experienced DNAemia, this association was not evaluated using multivariable analyses. Meanwhile, we found that CMV disease was associated with a strong hazard of negative outcomes among all patients, as well as the at-risk subgroup, which indicates a potential association in a larger study.…”
Section: Ta B L E 2 Cmv Infection and Disease Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytomegalovirus (CMV) remains an important cause of morbidity and mortality in solid organ transplant recipients (SOTR) 1 Rates of CMV infection and/or disease in pediatric SOTR vary from 8%–38% in heart recipients, 2–4 14%–22% in kidney recipients, 4–6 and 10%–40% in liver recipients 1,4,7,8 …”
Section: Introductionmentioning
confidence: 99%